Detection of former goaf and analysis of deformation characteristics of overburden in Dameidong coal mine - Wei, Zhan-Xi; Zhao, Meng; Xie, Fei-Hong; Cao, Sheng-Hong; Dong, Jian-Hui; Dong, Yang-Dan (Frontiers in Earth Science, 2023)
In order to study the law of strata subsidence in coal mine goaf and observe whether it has adverse effects on the surrounding buildings and people 's safety, this paper probes and analyzes the geological and hydrologic conditions of Dameidong coal mine in Qinghai province at the present stage, deduces the mining area of coal mine based on geological data, and studies the deformation law of coal seam opening by using discrete element simulation technology. The distribution range and depth of the mined-out area in Dameidong coal mine are explored by means of transient electromagnetic method. The results of geophysical exploration show that the mined-out subsidence area in Dameidong coal mine is within the scope of ovoid water-rich area, and the average buried depth of the mined-out area is estimated to be 90 meters. The discrete element numerical simulation was used to establish a model to study the change law of overburden after mining. The results show that the stress change in coal mining is mainly reflected at both ends of goaf, which is a stress concentration phenomenon. The deformation of overburden strata changes with the progress of mining process, and the deformation does not exceed the mining thickness, and the deformation of the five monitoring lines arranged in parallel along the surface presents a u-shaped distribution. The overburden strata in the middle of the goaf collapses, and the deformation Angle of the subsidence area is between 92°-129° and 40°-52°, respectively. It provides reference for further study on prevention and control of regional subsidence disasters.